Mobile Based Parking Application Using Extreme Programming (Xp) Method - Mochammad Alfar Budistia; Meriska Defriani; Irsan Jaelani (RISTEC : Research in Information Systems and Technology, 2023)
Vehicle care is one of the businesses that is quite profitable with quite large capital. However, with this capital it becomes a fairly large and long-term income, and from this capital every year the price of this capital will definitely increase because of the area of the land. However, in business, there is a problem that often occurs in each of these safekeeping, namely realtime accounting and data in photos and numbers. Then this research aims to make it civil in managing the daycare. The model and method used uses Extreme Programming (XP) development and, why did I take mobile programming because in this case study it is better for device users who are indeed flexible.The feasibility of this system is seen from the point of view of its functionality and according to the user from what is needed according to the case study. The programming language used is Java, and testing is to display the success of system functionality using a black box, then for modeling using the unified model language (UML) for flow using this system, the database used is firebase.The purpose of this research is to get a solution to the problems that exist in the place, namely in data collection and reporting to the owner by providing input within certain hours and then conveying it to the owner, with this application providing solutions to problems that occur at this research location.